2014
DOI: 10.1590/0004-282x20140151
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drugs patterns in elderly inpatients in a Brazilian tertiary center, Salvador, Brazil

Abstract: Epilepsy is very prevalent among elderly inpatients and treatment is far from ideal. Objective: To analyze prescribing patterns of antiepileptic drugs (AEDs) for hospitalized elderly with epilepsy, their relations with comorbidities and comedications. Method: We assessed prescription regimen of elderly patients that were under AED use for treatment of epileptic seizures, during hospitalization. One hundred and nine patients were enrolled. AED regimen was categorized into two groups: Group 1 defined as appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…A prior study was conducted to investigate prescribing patterns of AEDs for older adult inpatients with late-onset epilepsy and found that the most common AED prescribed to that population was phenytoin (53%) 12 , which is consistent with several studies also showing phenytoin as the most commonly prescribed AED (50-70%) 9,13 . Notwithstanding guidelines and expert consensus opinions advocating the use of newer AEDs in the treatment of epilepsy among older people, these patients still receive suboptimal treatment in clinical practice.…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…A prior study was conducted to investigate prescribing patterns of AEDs for older adult inpatients with late-onset epilepsy and found that the most common AED prescribed to that population was phenytoin (53%) 12 , which is consistent with several studies also showing phenytoin as the most commonly prescribed AED (50-70%) 9,13 . Notwithstanding guidelines and expert consensus opinions advocating the use of newer AEDs in the treatment of epilepsy among older people, these patients still receive suboptimal treatment in clinical practice.…”
Section: Introductionsupporting
confidence: 71%
“…To investigate trends in prescribing patterns of AEDs, the AEDs prescribed to the study cohort of older adult inpatients with late-onset epilepsy between 2015 and 2019 (Y2) were identified and these data were compared to results of the previous retrospective study on a similar population conducted between 2009 and 2010 (Y1) 12 . Patient characteristics were also analyzed to identify any risk factor for receiving suboptimal therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Older people with epilepsy use more co-medications than younger people [28]. In our cohort, around 25% of all patients took at least one medication that was potentially pro-convulsant.…”
Section: Co-medicationsmentioning
confidence: 76%
“…Levetiracetam, lamotrigine, gabapentin, and carbamazepine are recommended for elderly individuals with epilepsy . However, in reality, these recommendations are not followed; VPA and phenytoin are used widely in this population around the world, although most elderly individuals with epilepsy show focal‐onset seizures. VPA is also known to have a risk of inducing coagulopathy, and it should therefore be avoided for elderly patients because of the risk of stroke.…”
Section: Discussionmentioning
confidence: 99%